Desire and Reciprocal Violence in Absalom, Absalom! - Cobley, Evelyn (English studies in Canada, 1987)
D E S I R E A N D R E C I P R O C A L V I O L E N C E I N A B S A L O M , A B S A L O M ! EVELYN CO BLEY University of Victoria T h e story of the Sutpens in Absalom, Absalom!1strikes us as tragic because the characters seem doomed to destroy each other in spite of strong bonds of family, love, and friendship. Whatever happiness or success these char acters desire, their aspirations are always frustrated, leading to violence and destruction. The tragic outcome of the Sutpen story has variously been attributed to psychological flaws, to social or historical circumstances, to Greek or Biblical notions of destiny, or to existential absurdity.2 The most convincing explanation has undoubtedly been that Sutpen’s abstract "design" cannot accommodate miscegenation and is therefore responsible for the con flicts between personal and social moral demands. The critical consensus seems to contend that it was indeed the threat of miscegenation rather than the threat of incest that unravels Sutpen’s design; it follows, then, that the Sutpens are symptomatic of a social disease which had also been responsible for the defeat of the Confederates. Olga Vickery quite typically argues that it was " the shadow of the Negro" which separated " brother from brother, son from father, lover from beloved" 3 while Eric J. Sundquist adds that Absalom illustrates historically verifiable attitudes to a lost past as the source for both guilt and nostalgia.4 Such explanations are no doubt accurate, but they need to be supplemented by an analysis of character behaviour that goes beyond this traditional moral and social framework. The patterns of reciprocal violence in Absalom must be further investigated as the conse quence of mediated desire, an intersubjective process that has been discussed by René Girard in Mensonge romantique et vérité romanesque (1961), by Jacques Lacan in Ecrits (1966), and by Alexandre Kojève in Introduction à la lecture de Hegel ( 1947 ),5 These three theorists have been influential figures on the French intellectual scene, especially since they have reinter preted and challenged romantic notions of the human subject as an autono mous essence.6 Their arguments are relevant to an understanding of character behaviour in Absalom because each theorist maintains, in some what different terms, that the human subject becomes aware of itself only through identifications with others. Relationships between self and other E n g l is h S t u d ie s in C a n a d a , x i ii, 4, December 1987 are consequently not spontaneous but mediated by a third term which represents the desire of the other. For Girard, Lacan, and Kojeve human desire manifests itself as a triangular process which mobilizes patterns of both attraction and aggression. This Girard-Lacan-Kojeve framework per mits a close analysis of the reciprocal violence in Absalom and increases our appreciation for Faulkner’s complex understanding of human behaviour. A first impression of the Sutpens in Absalom is likely to convince us that these characters relate to each other in a relatively unproblematical fashion in that brother obviously loves sister, sister loves brother, brother loves brother, friend loves friend, and woman loves man. The complications that ruin these relationships are then attributable to what Lynn G. Levins calls "a doomed situation" which "makes a tragic ending inevitable" : Judith loving Bon, unaware that he is her brother; Bon loving Judith, but willing to sacrifice this love in exchange for a silent touch of recognition from Sutpen, his father; and Henry loving both his sister Judith and his brother Bon and knowing that he must prevent their marriage.7 This account suggests that the obstacles are external and circumstantial; it corresponds to a reading of unmediated relationships which Faulkner himself authorizes by indicating that each of the Sutpen children loved the other two: "Because Flenry loved Bon" (AA 89) ; " Because he [Bon] loved Judith" (AA 94); " he [Bon] loved Henry too" (AA 108) ; and "between Henry and Judith there had been a relationship closer than the traditional loyalty of brother and sister even" (AA 79). Judging from these pronounce ments...